Direct Laryngoscopy under Topical Anaesthesia and Superior Laryngeal Nerve Block for Laryngeal and Hypopharyngeal Lesions in ENT Patients - Arti, Dr; Jyoti, Deep; kumar, Neelam; Dolma, Kunzes; Jamwal, Padam Singh (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Direct laryngoscopy is a common procedure being done by otolaryngologists under general anaesthesia for various pathologies of the larynx and hypopharynx. Regional anaesthesia using topical spray and bilateral superior nerve block is an alternative for the direct laryngoscopy. Aim: To evaluate the effect of bilateral block of superior laryngeal nerve (SLN) and topical anesthesia in direct laryngoscopy for diagnostic purpose as well as for taking biopsies from the larynx and hypopharynx. Materials And Methods: This is a prospective study done on 20 patients in age group of 50 to 70 years with laryngeal and hypopharyngeal growth. All these patients underwent diagnostic direct laryngoscopy with biopsy under regional block which include bilateral superior laryngeal nerve block with 2% lignocaine and topical anaesthesia of oral cavity and transtracheal through cricothyroid membrane with 10% lignocaine spray and 4% lignocaine respectively. Result: Success rate in our study was 85% in supraglottic, transglottic, pyriform growth and only 15% in glottis and postcricoid growth based on assessment of hemodynamic stability and patients comfortable score before and after the procedure under regional block. Conclusion: Direct Laryngoscopy under topical anesthesia and superior laryngeal nerve block for biopsy is a good alternative to general anesthesia for the patients presenting in ENT with laryngeal and hypopharyngeal pathologies.